Energy Security – Quo vadis Europe? (Economic and Political Thought, 2010)
The author of the article discusses the issue of energy security startingwith a characteristic comment on Sascha Muller-Kraenner’s book titled“Energy Security – re-measuring the world”, going through a presentation ofselected European Union plans, ideas and activities in that respect and finallypresenting and examining a new Jerzy Buzek’s and Jacques Delors’ idea tocreate European Energy Community. The article discusses issues connectedwith dual mutually dependent complex of threats growing on the security axis,i.e. energy industry and ecology.There is also an analysis of the necessity to develop a common energystrategy and the issue of the present domination of particular interests of themember states which can have a highly destructive effect on the idea of theEuropean integration. Preparing the article, the author drew on his analysisof documents and current European Union and member states’ actions. Theconclusions draw readers’ attention to fears about a really common form ofaction of the member states due to their varied approach towards the issueand inability to develop a really common energy policy. The deliberationsled the author to a conclusion that the same sectoral integration that startedthe process of European Union creation in the 1950s can be the beginning of its end.